Experimental study on thermal management of data center with non-uniform heat load - Wei-Mon Yan; Hao Kao; Uzair Sajjad; Chun-Han Li; Saman Rashidi (Case Studies in Thermal Engineering)
Proper thermal management operations in data centers can save about 10 %–15 % of total energy consumption. In this study, a heat exchanger, ice water host, and cooling tower are used to compose the cooling system for the data center. Short distance and ceiling air supply are adopted to reduce the energy consumption of data center heat dissipation and maintain good cooling environment conditions in the data room. Rack Cooling Index (RCI), Return Temperature Index (RTI), and Supply Heat Index (SHI) are used for the measurement and evaluation of the system. The results show that because the small data room adopts short distance and ceiling air supply configuration, the hot and cold channels are isolated under the short-distance air supply channel. Hence, in the ideal range, SHI is less than 0.4 on behalf of its cold air, which is very little affected by hot air. Servers, which need to run on full load for a long time, can be placed in the bottom area of the cabinet to maintain a better working environment.